2012
DOI: 10.3382/ps.2012-02489
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of Salmonella typhimurium lipopolysaccharide and fumonisin B1 in broiler chickens

Abstract: The aim of this research was to evaluate the individual and combined effects of Salmonella typhimurium lipopolysaccharide (sLPS) and fumonisin B(1) (FB) on performance, relative weight of liver, biological parameters, and histological evaluation of several tissues from four hundred thirty-two 1-d-old male broiler chickens divided into 9 treatments according to the dose of FB (0, 100, or 200 mg/kg, from d 1 to d 28) and sLPS (0, 250, or 500 µg/application per bird, every other day, from d 15 to 27) administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…In addition, increased liver weight and liver relative weight after FB 1 exposure have been reported in other broiler chick studies (Ledoux et al, 1992). We observed an increased feed conversion rate, indicating that chicks need to consume more feed to produce the same weight gain as controls, whereas Rauber et al (2012) reported a similar result in Cobb chicks.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, increased liver weight and liver relative weight after FB 1 exposure have been reported in other broiler chick studies (Ledoux et al, 1992). We observed an increased feed conversion rate, indicating that chicks need to consume more feed to produce the same weight gain as controls, whereas Rauber et al (2012) reported a similar result in Cobb chicks.…”
Section: Discussionsupporting
confidence: 72%
“…To achieve the desired FB 1 contamination in the feed (100 mg/kg of feed), a Fusarium verticillioides (strain MRC 826) culture material containing 4850 mg/kg of FB 1 was incorporated into the diet (Rauber et al, 2012). Feed and water were provided ad libitum.…”
Section: Mycotoxin and Feed Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples were analyzed for total plasma proteins (TPP), albumin (Alb), total cholesterol (Chol), triglycerides (Tri), calcium (Ca), phosphorus (P), uric acid (UA), and C-reactive protein (CRP) levels, alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma glutamyltransferase (GGT), and alkaline phosphatase (AP) activity, using commercial kits (Labtest Diagnostica S.A., Vista Alegre, Lagoa Santa, Minas Gerais, Brazil) in a spectrophotometer. Additionally, free sphinganine and sphingosine levels in serum were analyzed for sphinganine-to-sphingosine ratio (SA:SO) calculation, according to Rauber et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary fumonisin B1 exposure caused a significant increase in the sphinganine-sphingosine (Sa:So) ratio starting from day 7 of the feeding trial. In addition to the nutritional parameters commonly employed as markers of toxicity in FB1 exposures; the increase in the Sa-So ratio has also been used as toxicity indicator in diverse experimental animal models [28]. The increased serum Sa-So ratio in the exposed Clarias gariepinus catfish juveniles was expected as FB 1 is structurally similar to sphinganine and sphingosine [29]- [31] and therefore competitively inhibits the enzyme ceramide synthase resulting in the accumulation of free sphinganine and to a lesser extent, sphingosine leading to an increase in the Sa-So ratio in exposed fish.…”
Section: Effects On Lipids Profilementioning
confidence: 99%